A STUDY OF TECHNOLOGY ADDICTION AND HEALTH IMPACTS AMONG COLLEGE STUDENTS - A, Arockia Doss; Manickam, P. Susai (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Currently, smartphones are an essential component of every person's life. A survey aimed at determining the variables contributing to health effects from smartphone use among college students in the 17–20 age range who are enrolled in undergraduate courses, respectively, is used to support this research. For the study, about 272 college students from two colleges in the Trichy district were recruited. Indicators of smartphone addiction and use, as well as their relationships to demographic and health behavior-related characteristics in college students, were examined in this study. Therefore, this research article offers methods for reducing the negative effects of smartphones as well as identifies the numerous health issues that College students use of smartphones has led to. The focus of this work will be on how a person's addiction to technology can negatively impact their social life and lead to both psychological and physical issues. For the research, the researcher has focused specifically on college students and their use of smartphones, as they are in the process of transitioning from adolescence to adulthood in terms of both psychological and physical development. Any adolescent going through this critical transitional stage needs to know that using a smartphone at this age increases the likelihood that it may negatively affect the adolescent's physical and mental health, which in turn affects their social well-being.